Exploring the barriers and opportunities for Muslim women in adventure tourism - Md Nasir, Maheran; Md Sawari, Siti Salwa (Khwarezm Publication, 2025)
Adventure tourism is attracting more Muslim women, yet they face challenges such as safety concerns, discrimination, and limited gender-sensitive services. This study, based on interviews with nine participants, highlights their preferences for halal food, prayer spaces, privacy, and female-only environments. Findings suggest that inclusive tourism development can enhance regional economies and aid poverty reduction through culturally sensitive services, improved infrastructure, and support for female-led tourism initiatives